Melodrama in Socialism and the Logic of the Revolution - Jukić, Tatjana (2013)
Taking up Only Human (Samo ljudi), the 1957 film by Branko Bauer, as a specimen story of melodrama in socialism, I argue that melodrama deregulates the attempts of state socialism to homogenize and hegemonize the revolution into a functional memory. It is thus in melodrama that a position opens for the analysis of how the revolution both informs and depletes the symbolic resources of socialism. While my discussion of this problem works with some of the insights suggested by Hannah Arendt in her book on revolution, it also proposes a critique of Arendt’s arguments, primarily from the point of view of psychoanalysis.